ChemInform Abstract: Preparation, Structural, Thermogravimetric and Spectroscopic Study of Magnesium Potassium Arsenate Hexahydrate. Issue 8 (February 2015) - Abdija, Zuldjevat; Najdoski, Metodija; Koleva, Violeta; Runcevski, Tomce; Dinnebier, Robert E.; Soptrajanov, Bojan; Stefov, Viktor
Abstract MgKAsO4·6H2O is precipitated from an aqueous KOH solution of KH2AsO4 by addition of aqueous MgSO4.